Determination of Water Soluble Vitamin in Fruits and Vegetables Marketed in Sindh Pakistan - Ismail, Fatima; Talpur, Farah N.; Memon, A.N. (Pakistan Journal of Nutrition, 2013)
Fresh vegetables and fruits are considered as a healthy source of water soluble vitamins. However water soluble vitamins may lose during washing and improper storage. Environmental factors such as light and temperature also have an effect on the moisture and vitamin contents of vegetables and fruits. Vitamins are needed for normal metabolic reactions in an appropriate amount, their deficiency or increased intake can lead to different irregularities in normal cellular metabolism. Pakistan is an agrarian country with about 21.9 million hectors of cultivation, of which Sindh province offers about 28554 acres .The production of vegetables and fruits is more than 50, 300 tons annually. The consumption of fruits and vegetables is increasing on daily basis as the people are getting more aware about the nutritional importance of fruits and vegetables. Vegetables and fruits supplies from the fields of harvesting to the markets are continuously in the exposure of environmental factors for example. Light intensity, traffic pollution which directly influence the moisture contents and ultimately reduces the water soluble vitamins contents. The vitamin contents also depend on the rate of the maturity of the vegetables and fruits as the early reaping is a common practice of the local farmers to get more economical benefits. Vegetables and fruits nutrients determination on monthly basis is a common practice in developed countries but such practices are rare in developing countries like Pakistan. Therefore the objective of the current study was the determination of vitamin B complex (B1, B2, B3, B6, B9) from the selected vegetables and fruits consume frequently in the region of Sindh, Pakistan. The HPLC analysis of acid hydrolysis samples showed that thiamin (B1) was found in the range of 0.02-0.18mg/100gm, riboflavin (B2) 0.016-0.2mg/100gm, niacin (B3) 0.01-0.1mg/100gm while pyridoxine (B6) was determined as 0.06-0.28mg/100gm and folate (B9) 0.016-0.19mg/100gm which have been determined lower than the recommended ranges.